Investigation of the Association of miRNA-499 , miRNA-146a , miRNA-196a2 Loci with Hepatocellular Carcinoma Risk: A Case-Control Study Involving 1507 Subjects - Zhang, Sheng; Chen, Lizhu; Wang, Yafeng; Tang, Weifeng; Chen, Yu; Liu, Longgen (DNA and cell biology, 2020)
' ( ) loci may influence hepatocellular carcinoma (HCC) development. Many recent studies have assessed the relationship between , , and loci and HCC risk. However, the observed results are conflicting. A total of 584 HCC patients and 923 age- and sex-matched controls were recruited. The correlation of rs3746444, rs2910164, and rs11614913 with HCC development was assessed. In the <53-year-old subgroup, a correlation of the rs2910164 locus with HCC risk was found (GG/CG vs. CC: adjusted = 0.011, GG vs. CC: adjusted = 0.021 and CG vs. CC: adjusted = 0.027). The association between rs2910164 and the risk of HCC was also found in the never smoking (GG/CG vs. CC: adjusted = 0.011 and CG vs. CC: adjusted = 0.018). Using false-positive report probability method and power value, we identified that rs2910164 conferred a risk to HCC in the <53-year-old and never-smoking subgroups. In conclusion, this study indicates rs2910164 may be a risk factor for HCC, especially in the <53-year-old and never-smoking subgroups.